The Conception of Financial Management and Educational Financing - Muhamad Ikbal; Muhammad Aminullah; Hendy Aldian (Electronic Journal of Education, Social Economics and Technology, 2025)
The purpose of this study is to explain the basic concepts of financial management, costs, and Islamic education financing. This research uses a qualitative approach with a library study type. The data sources are obtained from books, journals, and scientific papers. The data analysis technique uses the Miles and Huberman approach, which consists of data reduction, data verification, and drawing conclusions. The research results show that management plays an important role in improving the quality of education, particularly in the financial management of educational institutions. Educational management must be well implemented to advance educational institutions, and effective and efficient financial management greatly supports the achievement of educational goals. The process of financial management in education includes planning, implementation, and evaluation, involving the management of financial resources such as budgets, accounting, and financial auditing. With proper implementation, educational financial management can help educational institutions achieve optimal and efficient results. The meaning of financial management and education financing involves a series of activities that include managing the finances of educational institutions. The implications of this research refer to the understanding of financial management and education financing. It emphasizes the importance of institutions understanding these concepts, which will lead to transparency in funding and accountability.